Chimeric derivatives of functionalized amino acids and α-aminoamides: Compounds with anticonvulsant activity in seizure models and inhibitory actions on central, peripheral, and cardiac isoforms of voltage-gated sodium channels. Issue 13 (1st July 2015) - Torregrosa, Robert; Yang, Xiao-Fang; Dustrude, Erik T.; Cummins, Theodore R.; Khanna, Rajesh; Kohn, Harold
Graphical abstract: Abstract: Six novel 3″-substituted ( R )- N -(phenoxybenzyl) 2- N -acetamido-3-methoxypropionamides were prepared and then assessed using whole-cell, patch-clamp electrophysiology for their anticonvulsant activities in animal seizure models and for their sodium channel activities. We found compounds with various substituents at the terminal aromatic ring that had excellent anticonvulsant activity. Of these compounds, ( R )- N -4′-((3″-chloro)phenoxy)benzyl 2- N -acetamido-3-methoxypropionamide (( R )-5 ) and ( R )- N -4′-((3″-trifluoromethoxy)phenoxy)benzyl 2- N -acetamido-3-methoxypropionamide (( R )-9 ) exhibited high protective indices (PI = TD50 /ED50 ) comparable with many antiseizure drugs when tested in the maximal electroshock seizure test to mice (intraperitoneally) and rats (intraperitoneally, orally). Most compounds potently transitioned sodium channels to the slow-inactivated state when evaluated in rat embryonic cortical neurons. Treating HEK293 recombinant cells that expressed hNaV 1.1, rNaV 1.3, hNaV 1.5, or hNaV 1.7 with ( R )-9 recapitulated the high levels of sodium channel slow inactivation.